Status Kewarganegaraan dalam Hukum Islam: Studi Kasus Muslim Minoritas di Negara Non-Islam - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur; Ananda Aulia; Rosyidatul Husna; Gayatri Kartika (International Forum of Researchers and Lecturers, 2025)
This article discusses citizenship status in Islamic law, focusing on case studies of Muslim minorities in non-Islamic countries, while considering the dynamics of national law and human rights. The research highlights that in Islamic law, citizenship is often associated with membership in the ummah, although modern Muslim states have adopted contemporary citizenship systems. Developments in Indonesian citizenship policies in the last five years, particularly concerning migration and the rights of foreign nationals married to Indonesian citizens, are also analyzed. However, the implementation of these policies faces challenges due to inconsistencies between national law and Islamic principles related to religious identity. The perspective of Islamic law emphasizes the safeguarding essential rights and human worth, in addition to fairness in the treatment of all individuals. The integration of muslim communities residing in western nations poses challenges in distinguishing the majority from extremist minorities. Additionally, equality, the liberty to make individual choices, and partnership are seen as key elements in shaping the societal lives of muslims across western regions. Therefore, a comprehensive understanding of the interaction between national laws and Islamic principles is needed to guarantee the safeguarding of the rights of muslim minorities worldwide.